Composition and distribution of plankton communities in the Atlantic sector of the Southern Ocean - Kasyan, Valentina V.; Bitiutskii, Dmitrii G.; Mishin, Aleksej V.; Zuev, Oleg A.; Murzina, Svetlana A.; Sapozhnikov, Philipp V.; Kalinina, Olga Yu.; Syomin, Vitaly L.; Kolbasova, Glafira D.; Voronin, Viktor P.; Chudinovskih, Elena S.; Orlov, Alexei M. (Diversity, 2022)
In recent decades, the waters off the Antarctic Peninsula and surrounding region have undergone a significant transformation due to global climate change affecting the structure and distribution of pelagic fauna. Here, we present the results of our study on the taxonomic composition and quantitative distribution of plankton communities in Bransfield Strait, Antarctic Sound, the Powell Basin of the Weddell Sea, and the waters off the Antarctic Peninsula and South Orkney Islands during the austral summer of 2022. A slight warming of the Transitional Zonal Water with Weddell Sea influence (TWW) and an increase in its distribution area was detected. Among the pelagic communities, three groups were found to be the most abundant: copepods Calanoides acutus, Metridia gerlachei, and Oithona spp., salpa Salpa thompsoni, and Antarctic krill Euphausia superba. Euphausiids were found in cases of low abundance, species diversity, and biomass. In the studied region, an increase in the amount of the salpa S. thompsoni and the euphausiid Thysanoessa macrura and the expansion of their distribution area were observed. Significant structural shifts in phytoplankton communities manifested themselves in changes in the structure of the Antarctic krill forage base. The composition and distribution of pelagic fauna is affected by a combination of environmental abiotic factors, of which water temperature is the main one. The obtained results have allowed us to assume that a further increase in ocean temperature may lead to a reduction in the number and size of the Antarctic krill population and its successive replacement by salps and other euphausiids that are more resistant to temperature fluctuations and water desalination.